Pengaruh Pengetahuan Produk dan Daya Tarik Promosi terhadap Minat Menggunakan Go-pay pada Kalangan Mahasiswa - Tuti Susanti; Rose Rahmidani (Jurnal Ecogen, 2022)
The purpose of this study was to determine the effect of product knowledge and promotional attractiveness on interest in using Go-pay among Universitas Negeri Padang students. This type of research is causative. The population in this study were Universitas Negeri Padang students. The number of research samples was 96 people and selected using the purposive sampling technique. The data used is the type of primary data obtained through distributing questionnaires to Universitas Negeri Padang students with predetermined criteria. The analytical method used is multiple regression analysis using SPSS 16. The results show that (1) product knowledge has a significant effect on interest in using Go-pay, (2) Promotional attractiveness has a significant effect on interest in using Go-pay. Keywords : product knowledge, promotional appeal, interest